A Phase 3, 1-Year, Open-Label Trial of Valbenazine in Adults With Tardive Dyskinesia. Issue 6 (November 2019) - Marder, Stephen R.; Singer, Carlos; Lindenmayer, Jean-Pierre; Tanner, Caroline M.; Comella, Cynthia L.; Verghese, Cherian; Jimenez, Roland; Liang, Grace S.; Burke, Joshua; O'Brien, Christopher F.
Abstract: Purpose/Background: Valbenazine is approved to treat tardive dyskinesia (TD) in adults. KINECT 4 (NCT02405091) was conducted to explore the long-term effects of once-daily valbenazine in patients with TD. Methods/Procedures: The study included a 48-week, open-label treatment period and 4-week washout. Dosing was initiated at 40 mg/d, with escalation to 80 mg/d at week 4 based on efficacy and tolerability. Standard safety methods were applied, including treatment-emergent adverse event (TEAE) reporting. Valbenazine effects on TD were assessed using the Abnormal Involuntary Movement Scale (AIMS), Clinical Global Impression of Change-TD, and Patient Global Impression of Change. Findings/Results: After week 4, <15% of all participants had a serious TEAE (13.7%) or TEAE leading to discontinuation (11.8%). Participants experienced TD improvements during long-term treatment as indicated by mean change from baseline to week 48 in AIMS total score (sum of items 1–7, evaluated by site raters) with valbenazine 40 mg/d (−10.2 [n = 45]) or 80 mg/d (−11.0 [n = 107]). At week 48, most participants had ≥50% improvement from baseline in AIMS total score (40 mg/d, 90.0%; 80 mg/d, 89.2%), Clinical Global Impression of Change-TD rating of much or very much improved (40 mg/d, 90.0%; 80 mg/d, 95.9%), and Patient Global Impression of Change rating of much or very much improved (40 mg/d, 90.0%; 80 mg/d, 89.2%). No dose effects were apparent by week 36. Week 52 results indicated some loss of effect after washout. Implications/Conclusions: Valbenazine was generally well tolerated, and no new safety concerns were detected. Substantial clinician- and patient-reported improvements were observed in adults with TD who received once-daily valbenazine for up to 48 weeks. Abstract : Supplemental digital content is available in the text.